Decreased Tongue Volume Post Radiation. (August 2020) - Garber, David; Rotsides, Janine; Abu-Ghanem, Sara; Bandler, Ilana; Smith, Amy; Oyfe, Irina; Swahn, Dawn-Marie; Hagiwara, Mari; Amin, Milan; Johnson, Aaron M.
Objectives: To evaluate volume changes within the tongue post chemoradiation therapy (CRT) Study Design: Retrospective review Setting: Academic Medical Center Subjects and Methods: Subjects included 19 patients that received CRT as the primary treatment for tonsillar or hypopharynx squamous cell carcinoma. Tongue volumes were calculated by three raters from thin slice computed tomography images collected before treatment and up to 29 months post-CRT. Body mass index (BMI) was also collected at each time point. Results: Inter-rater reliability was high with an ICC of 0.849 (95% CI = 0.773, 0.905). Linear mixed effects modeling showed a mean decrease of 0.45 cm 3 (standard error of the mean [SEM] = 0.11) in tongue volume per month post-CRT ( P < .001). However, the addition of BMI to the model was significant (χ 2 (4) = 25.0, P < .001), indicating that BMI was a strong predictor of tongue volume, with a mean decrease of 1.75 cm 3 (SEM = 0.49) in tongue volume per unit decrease in BMI ( P < .001) and reducing the post-CRT effect on tongue volume decrease per month to 0.23 cm 3 ( P = .02). BMI significantly ( P < .001) decreased by 0.11 units (SEM = 0.02) per month post radiation. Conclusion: Tongue dysfunction and decreased tongue strength are significant contributors to the dysphagia that patients experience after receiving CRT. In this study, both tongue volume and BMI decreased post-CRT; therefore, BMI could potentially be used as a predictor of tongue volume post-CRT.